PERTANGGUNGJAWABAN PIDANA TERHADAP ANAK PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA (Studi Putusan Nomor 7/Pid/Sus-Anak/2015/PN. Kabanjahe) - Hade Brata; Madiasa Ablisar; Suhaidi Suhaidi; Marlina Marlina (Universitas Sumatera Utara, 2017)
ABSTRACT Against children who do the criminal act would have done legal action or legal proceedings, which in the legal action, which is still more kids on the protection of the rights of the child in each level of the check, where it is based because within a child's inherent dignity, dignity, and rights of the child as befits a man should uphold high. In this research are discussed regarding criminal liability against committing criminal assassination plan, where judges decide the matter a criminal act planned to murder committed by children by giving a verdict in the form of imprisonment, of course it is interesting to be discussed and done research on it. Keywords: Criminal Liability, Children, Murder Plan